Growth and characterization of heteroepitaxy ZnO thin film on sapphire substrate with ion implantation followed by thermal oxidation-some preliminary results - Trịnh, Thị Tú Anh (2023)
ZnO thin film is one of the metal oxide semiconductors which are widely used in light emitting/ laser applications. Recently, ZnO has gained a new substantial interest primarily because of its potentialities for spintronic, as predicted by Dielt et. al. [1]. Methods for fabricating ZnO include metal-organic chemical vapor deposition, pulsed laser deposition, electron beam physical vapor deposition, molecular beam epitaxy, ion implantation, etc. Among them, ion implantation has several advantages such as easy and precise control of the dopant concentration, elimination of the contamination and avoidance of the secondary phase. In the previous studies, ZnO films were formed in transparent insulators such as silica glass SiO2 [2], MgO [3] by several methods. In the present research, we employed ion implantation method combined with thermal oxidation to fabricate ZnO thin film on sapphire substrate. X-ray diffraction (XRD) and Auger Electron Spectroscopy (AES) were applied to characterize the structure of these films.